2008
DOI: 10.1007/s10495-008-0226-5
|View full text |Cite
|
Sign up to set email alerts
|

BimL displacing Bcl-xL promotes Bax translocation during TNFα-induced apoptosis

Abstract: Bcl-2 family proteins are implicated as essential regulators in tumor necrosis factor-alpha (TNFalpha)-induced apoptosis. Bim(L), a BH3-only member of Bcl-2 family, can directly or indirectly activate the proapoptotic Bax and the subsequent mitochondrial apoptotic pathway. However, the molecular mechanism of Bim(L) activating Bax activation during TNFalpha-induced apoptosis is not fully understood. In this study, the role of Bim(L) in Bax activation during TNFalpha-induced apoptosis was investigated in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…Our work demonstrates that the NF-B family of proteins is necessary for MN survival; knockdown of these proteins probably deregulates gene expression of proteins that exert their function upstream of the mitochondria. It has been recently demonstrated that the BH3-only protein, Bim, displaces Bcl-x L in the mitochondria and promotes Bax translocation during TNF␣-induced apoptosis in PC12 cells (Zhang et al, 2008). In our model, we observed in shRelA-treated cultures an increase of Bim protein level, suggesting that this protein could be regulating the apoptotic cell death process caused by the blockade of NF-B signaling.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Our work demonstrates that the NF-B family of proteins is necessary for MN survival; knockdown of these proteins probably deregulates gene expression of proteins that exert their function upstream of the mitochondria. It has been recently demonstrated that the BH3-only protein, Bim, displaces Bcl-x L in the mitochondria and promotes Bax translocation during TNF␣-induced apoptosis in PC12 cells (Zhang et al, 2008). In our model, we observed in shRelA-treated cultures an increase of Bim protein level, suggesting that this protein could be regulating the apoptotic cell death process caused by the blockade of NF-B signaling.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, Bim displaces Bcl-x L in the mitochondria and promotes Bax translocation during TNF␣-induced apoptosis (Zhang et al, 2008). In this context, we decided to analyze whether Bim protein levels changed when the canonical NF-B pathway was knocked down.…”
Section: Effect Of Nf-b Pathway Inhibition On Bim Protein Levelmentioning
confidence: 99%
“…Bcl-2 directly interacts with the proapoptotic molecules in the mitochondrion to antagonize apoptosis. 34,35) The interaction between the Bcl-2 protein and the proapoptotic proteins may determine the fate of a cell. Thus, we first detected the expression of Bcl-2 in the kidney of STZ and non-STZ treated rats with or without minocycline-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the activation of caspase cascade, of three main pathways including DR-ligand complex-activated caspase-8 pathway, the mitochondria dependent pathway characterized by mitochondrial membrane permeability change according to pro-apototic Bax/anti-apoptotic Bcl-2 ratio, consecutive cytochrome c release and subsequent activation of apoptosome-associated caspases-9 and -3 and the endoplasmic reticulum(ER)-specific apoptotic pathway involving caspase-12 activation, former two pathways are more noteworthy regarding both apoptotic pathways in various cancer cells and considered a potential target of developing new anticancer drugs [51][52][53] where induction of apoptosis critically depends on upregulation of proapoptotic caspases known as executioners of apoptosis [54][55][56] . In the expression of apoptosis related proteins, SVT with TRAIL in HT29 cells represented increased Bax/Bcl-2 ratio, subsequently upregulated intrinsic apoptotic pathway related cleaved caspase-9, -3 as well as activated extrinsic DR-mediated apoptotic pathway related caspase-8, suggesting SVT exerts substantial influence upon bilateral apoptosis in them nevertheless of TRAIL resistance (Fig.…”
Section: ⅳ Discussionmentioning
confidence: 99%